Tingkat Kepuasan Pasien terhadap Pelayanan Rawat Jalan Poli Penyakit Dalam pada Rsup Dr. Sitanala Tangerang - Florianus Reu (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
Outpatient services are an integral component of the health service delivery system in hospitals which provides and plays an important role in continuity of patient care and improving service quality. Patients have a level of satisfaction according to their respective standards for the services they have received. Patient satisfaction is a very important and comprehensive part of the quality of health services provided. Patient satisfaction is a level of patient feeling that arises as a result of the performance of the health services they have obtained after the patient compares it with their expectations. The aim of this research was to determine the satisfaction level of internal medicine outpatients available at RSUP Dr. Sitanala Tangerang using 5 dimensions of quality. The research method is quantitative descriptive research using questionnaire survey techniques. This study used a cross sectional approach because the sampling was carried out simultaneously over the same period of time using a non-random sampling method using convenience sampling of patients who came to receive outpatient services at the internal medicine clinic. With the results of the physical evidence (Tangibles) dimension of 90%, the Responsiveness dimension of 87,9%, the reliability dimension of 89,6%, the Assurance dimension of 93%, and the Attention (Emphaty) dimension of 90,8%.